Chlamydia pecorum Associated With an Outbreak of Infectious Keratoconjunctivitis in Semi-domesticated Reindeer in Sweden - Sánchez Romano, Javier; Leijon, Mikael; Hagström, Åsa; Jinnerot, Tomas; Rockström, Ulrika K.; Tryland, Morten (Frontiers in Veterinary Science, 2019)
Infectious keratoconjunctivitis (IKC), the most common ocular disease in ruminants worldwide, has affected semi-domesticated Eurasian reindeer (Rangifer tarandus tarandus) for over 100 years, both as individual cases and in outbreaks affecting tens to hundreds of animals. Recurrent IKC outbreaks have been affecting a semi-domesticated reindeer herd in Östra Kikkejaure (Norrbotten county, Sweden) from 2014. The latest episode of these recurrent outbreaks, in winter 2016/2017, was investigated in this study. Clinical findings were in line with previous reports of IKC in semi-domesticated reindeer and the clinical signs displayed by the affected animals (n = 30) included increased lacrimation, follicular conjunctivitis, purulent secretions around the affected eyes and corneal edema. Laboratory analyses of the samples revealed the presence of Chlamydiaceae in most samples obtained from the clinically affected animals (98.3 %, n = 60), but also a high seroprevalence of cervid herpesvirus 2 (CvHV2) antibodies (56.6 %, n = 53). Moraxella bovoculi was isolated from nine IKC-affected animals during the outbreak (45.0 %, n = 20). All affected animals were treated with long-acting antibiotics and recovered from the disease, testing negative for the presence of Chlamydiaceae DNA by PCR 16 days and three months after the initial treatment. For the first time, Chlamydia pecorum was identified in semi-domesticated reindeer, and the involvement of Chlamydiaceae in a clinical outbreak of IKC is reported. The CvHV2 seroprevalence (56.6 %) and the data obtained from a previous outbreak in 2014 also suggest the involvement of the reindeer alphaherpesvirus in the recurrent outbreaks.